Multilingual COVID-19 Information Videos - Bezuidenhout, Louise; McNaughton, Anna; Havemann, Johanna (My University, 2020)
We propose to address a lack of CODIV-19 information in local languages with short, consistent messages provided in as many regional/local languages as possible. For that, we need help of researchers and other communicators. This is a proposal to create 2-minute videos in as many languages as possible that present a consistent message about COVID-19, containment strategies and practical health information.
Keywords: science literacy; COVID-19; Video